2001
DOI: 10.1023/a:1012307324782
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Molecular characterization has been accomplished for five members of the peroxidase gene family in French bean. The most important of these, designated FBPI, corresponds to the isoform believed to be responsible for the apoplastic oxidative burst demonstrated by suspension-cultured cells in response to fungal elicitor. Identification was made by a complete match of six peptide sequences derived from the native protein to the translated sequence of the cDNA. Modelling of the surface structure in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Class III peroxidases are enzymes secreted into the apoplast, where they oxidize (take electrons from donor molecules) phenolics, lignin precursors or other secondary metabolites. They also oxidize the growth hormone auxin, as well as other substrates ( Gaspar et al, 1982 ) and produce hydrogen peroxide ( Blee et al, 2001 ) and hydroxyl radicals ( Chen and Schopfer, 1999 ), two activated oxygen species involved in oxidative burst and in cell elongation. It is a multigenic complex family ( Hiraga, 2001 ), with roles in several plant developmental processes, including regulation of cell elongation, cell wall construction and defense against pathogens ( Mika et al, 2004 ; Passardi et al, 2004a ).…”
Section: Discussionmentioning
confidence: 99%
“…Class III peroxidases are enzymes secreted into the apoplast, where they oxidize (take electrons from donor molecules) phenolics, lignin precursors or other secondary metabolites. They also oxidize the growth hormone auxin, as well as other substrates ( Gaspar et al, 1982 ) and produce hydrogen peroxide ( Blee et al, 2001 ) and hydroxyl radicals ( Chen and Schopfer, 1999 ), two activated oxygen species involved in oxidative burst and in cell elongation. It is a multigenic complex family ( Hiraga, 2001 ), with roles in several plant developmental processes, including regulation of cell elongation, cell wall construction and defense against pathogens ( Mika et al, 2004 ; Passardi et al, 2004a ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of enzymes are involved in the lignin/lignan branch of the phenylpropanoid pathway, in most cases, encoded by small gene families. Only few sequences for lignin peroxidases were available for common bean at the beginning of this study (Blee et al, 2001). The flavonoid/anthocyanin branch, which encodes the enzymes involved in the production of anthocyanins and proanthocyanidins (condensed tannins) associated with seed coat color as well as different flavonoids involved in nodulation and plant defense, is probably the most studied segment of the phenylpropanoid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The result indicated that the high activities of these enzymes resulted in the relatively low content of H 2 O 2 at 0.5 and 6 h. But the content of H 2 O 2 and the activities of these enzymes were all higher than control at three time points. Though POD has also been shown to efficiently produce H 2 O 2 (Blee et al 2001;Bolwell et al 2002), in poplar plants after herbivory damage it mainly The content of H 2 O 2 in herbivore-wounded leaves (hw) after DPI treatment. The contents in control leaves (ck), herbivorewounded leaves (hw), leaves treated only by DPI, and herbivorewounded leaves after DPI treatment (hw ?…”
Section: Discussionmentioning
confidence: 99%